Monopoly in Real Life - The Housing Market, Finance and Inequality - Dirk Baur (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper uses a simple model based on the board game Monopoly to analyze the drivers of house prices and wealth inequality. Simulations show that inequality generally builds up fast even if players have equal starting conditions and house prices are stable; rising house prices imply more extreme inequality. An extension of the classical game with interest rates and debt-financing further shows that low interest rates facilitate a property carry trade and increase house prices and inequality by more than high interest rates. The simulations also demonstrate a first-mover advantage both within a generation and between generations and the non-exogenous nature of wealth accumulation, i.e. without new money owing into the housing market, house prices do not go up and wealth differences are less extreme. Overall, despite the model's simplicity it presents striking similarities with empirical evidence.
Keywords: D10; D31; D42; D63; E47; E58; R30; 330; house prices; debt; inequality; monetary policy; board game Monopoly; Cantillon effect; Ponzi scheme